Nematoda fauna of some charadriiformes from Czech Republic (region Brno) - Okulewicz, A; Koubek, P (Wiadomości Parazytologiczne, 1994)
Examination of 10 bird species of the family Charadriidae have revealed the following nematode species: Strongyloides turkmenicus, Syngamus palustris, S. trachea, Porrocaecum semiteres, Tetrameres dubia, Eucoleus contortus and Capillaria sp. Three of them: S. turkmenicus, S. palustris and T. dubia parasitizing those hosts were found the first time in Czechoslovakia. Tringa glareola was found a new host for S. palustris.
Keywords: Polsko; Animals; Czech Republic; Poland; zvířata; ženské pohlaví; Nematoda; Female; hlístice; Birds; ptáci; Česká republika